2006
DOI: 10.1007/s00018-006-6272-7
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic mechanisms in myeloproliferative disorders

Abstract: Myeloproliferative disorders (MPDs) are clonal haematopoietic malignancies involving the abnormal proliferation of myeloid lineages. The World Health Organisation (WHO) classification of haematopoietic malignancies distinguishes MPDs from myelodysplastic/ myeloproliferative disorders and systemic mastocytosis. These malignancies frequently involve constitutive tyrosine kinase activity, resulting from either oncogenic fusion protein production or from point mutations. Chronic myelogenous leukaemia is the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 122 publications
4
69
0
6
Order By: Relevance
“…These results imply a role for cooperating mutations in the pathogenesis of JAK2 V617F-positive MPNs and support the hypothesis that dosage of JAK2 contributes to the disease phenotype in which an increased constitutive activation of JAK2 provides a proliferative advantage. 138 Cytogenetics, when combined with JAK2 mutational screening, has also provided evidence of a common clonal origin for at least some cases of MPNs and AML and for the fact that JAK2 mutations may not be the initiating event. Theocharides et al, 139 for example, reported a single case with JAK2-V617F-positive PMF in which JAK2-V617F was absent from the blasts at the time of transformation.…”
Section: Cytogenetics and Jak2 Mutationsmentioning
confidence: 99%
“…These results imply a role for cooperating mutations in the pathogenesis of JAK2 V617F-positive MPNs and support the hypothesis that dosage of JAK2 contributes to the disease phenotype in which an increased constitutive activation of JAK2 provides a proliferative advantage. 138 Cytogenetics, when combined with JAK2 mutational screening, has also provided evidence of a common clonal origin for at least some cases of MPNs and AML and for the fact that JAK2 mutations may not be the initiating event. Theocharides et al, 139 for example, reported a single case with JAK2-V617F-positive PMF in which JAK2-V617F was absent from the blasts at the time of transformation.…”
Section: Cytogenetics and Jak2 Mutationsmentioning
confidence: 99%
“…1 Typically, disease progression in CMD is reflected by an increase of immature cells and growing chromosomal instability. Constitutive activation of tyrosine kinases ABL, FGFR1, JAK2, PDGFRa or PDGFRb has been identified as a common underlying pathomechanism in CMD.…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive activation of tyrosine kinases ABL, FGFR1, JAK2, PDGFRa or PDGFRb has been identified as a common underlying pathomechanism in CMD. [1][2][3][4][5] Structurally, with the exception of ABL these tyrosine kinases belong to the receptor tyrosine kinase family and consist of an extracellular ligand binding domain, a transmembrane domain, an often autoinhibitory cytoplasmic juxtamembranous domain and a catalytically active C-terminal domain.…”
Section: Introductionmentioning
confidence: 99%
“…The 2008 ECMP classification separated the JAK2 wild type MPN into MPL mutated ET/MF as the second and JAK2 wild type hypercellular ET associated with primary granulocytic megakaryocytic myeloproliferation (PMGM) as the third distinct MPN disease. [16,48,49]. [22][23][24][25][26][27][28][29][30] and the 2008 ECMP classification respectively are based on three specific bone marrow histology criteria: 1) the presence of large dysmorphic megakaryocytes with immature cytoplasm and immature cloud-like nuclei not seen in ET and PV, 2) increased granulopoiesis but never disturbed in maturation and 3) no features of PV with relatively decreased erythropoiesis.…”
Section: Hannover Bone Marrow Classification Of the Mpds Et Pv And Pmgmmentioning
confidence: 99%